2021
DOI: 10.3390/ma14237462
|View full text |Cite
|
Sign up to set email alerts
|

The Friction of Structurally Modified Isotactic Polypropylene

Abstract: The purpose of studies was to analyse an impact of heterogeneous nucleation of modified isotactic polypropylene (iPP) on its tribological properties. The iPP injection molded samples, produced by mold temperature of 20 and 70 °C, were modified with compositions of two nucleating agents (NA’s), DMDBS creating α-form and mixture of pimelic acid with calcium stearate (PACS) forming β–phase of iPP, with a total content 0.2 wt.% of NA’s. A polymorphic character of iPP, with both, monoclinic (α) and pseudo-hexagonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Polarized optical microscopic observation showed a significant influence of the spherulite size of iPP after treatment (Figure b). When PP-treated with higher temperatures (OPP125), the crystal size of the treated sample became slightly smaller because of cooling-induced crystallization after heat treatment . However, only a few crystals can be observed in OPP150.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polarized optical microscopic observation showed a significant influence of the spherulite size of iPP after treatment (Figure b). When PP-treated with higher temperatures (OPP125), the crystal size of the treated sample became slightly smaller because of cooling-induced crystallization after heat treatment . However, only a few crystals can be observed in OPP150.…”
Section: Resultsmentioning
confidence: 99%
“…When PP-treated with higher temperatures (OPP125), the crystal size of the treated sample became slightly smaller because of cooling-induced crystallization after heat treatment. 55 However, only a few crystals can be observed in OPP150. It is well-known that whether or not a polymer can crystallize depends on its molecular structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was found that the aging time of PP-Rβ, which has a better fatigue crack expansion resistance, was 30% higher than that of PP-Rα [ 15 ]. Moreover, the effect of β-crystals on the friction coefficient [ 16 ] is less than that of α-crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on various aspects of the sliding surface, including tribological investigations of different polymers and the role of mating surfaces [1]. Additionally, the literature provides results of coefficient of friction (COF) measurements for various polymers employed as plain bearings [2,3]. Enhancing tribological parameters and mechanical properties remains a popular research topic.…”
Section: Introductionmentioning
confidence: 99%